Is endocrine and exocrine function improved following duodenal preserving pancreatic head resection over whipple for chronic pancreatitis?. Issue 7 (July 2022) - Turner, Kevin M.; Delman, Aaron M.; Johnston II, Michael E.; Hanseman, Dennis; Wilson, Gregory C.; Ahmad, Syed A.; Patel, Sameer H.
Abstract: Background: The aim of our study was to evaluate the rates of treatment for post-operative exocrine pancreatic insufficiency (EPI) and diabetes mellites (DM) between Duodenal Preserving Pancreatic Head Resections (DPPHR) and Pancreaticoduodenectomy (PD) from a prospectively maintained database of patients with chronic pancreatitis. Methods: 104 patients were identified for inclusion, 62 of whom underwent DPPHR and 42 underwent PD. Study endpoints included changes in treatment for EPI and DM. Results: In the DPPHR group, the vast majority (n = 55) received a Frey procedure, with a small minority of patients undergoing a Beger procedure (n = 4) or Berne modification (n = 3). Patients in the DPPHR group had a lower rate of new persistent treatment for EPI post-operatively compared to patients who underwent PD (28.0% vs. 76.5%, p = 0.002). There was no difference in the rate of new onset DM, with low rates of new insulin dependent diabetics in both groups. Both groups had equal efficacy in terms of pain control, with 67.7% of the DPPHR group and 61.9% of the PD group remaining opioid free at long-term follow-up (p = 0.539). Conclusion: In patients with head-predominant chronic pancreatitis, DPPHR was associated with reduced rates of new EPI treatment and similar endocrine function compared with PD. Graphical abstract: Image 1